Kitle sporunun teşviki açısından öncelikli spor dallarının belirlenmesi ve tesis politikası: Manisa ili uygulaması - Gümüş, Sevilay (My University, 2007)
1.ÖZET Çalışmamız 2006 yılı nisan ayında ... bireye rast gele örnekleme yöntemiyle anket uygulanarak gerçekleştirildi. Ortaya çıkan veriler test edilerek tespit edildi. Kullanılan testler: aritmetik ortalama, yüzdelik oranlar,sınıf aralığı ve ki-kare şeklindedir. Verilerin analiz edilip yorumlanmasıyla Manisa ilinde hayatını sürdüren bireylerin spora olan yakınlıkları, uğraştıkları spor dalları ve spor tesisleri hakkındaki görüşleri ortaya çıkarılmıştır. Çalışmamız sonucunda; Manisa halkının demografik unsurları ile sosyo-kültürel yapısı, spora duyulan ilgi düzeyini şekillendirmektedir. Ancak ana hatları ile irdelendiğinde yöre halkının spora bakış açısı olumludur. Kitle sporunun teşvikinde, yaygınlaştırılmasında ve spor tesislerinin çoğaltılmasında yöre insanının hem yerel ve hem de merkezi yönetimden önemli beklentileri vardır. 2

DETERMINING THE PRIORITY SPORT BRANCHES TO PROMOTE THE MASS SPORTS AND STRATEGY FOR SPORTS FACILITIES: As Applied in the city of Manisa. This thesis, aims at analyzing the inclination of the people living in the city of Manisa in order to find out their familiarity with sports, identify which sport branches they deal with, and hear their remarks about sports facilities in Manisa. This study took place in April 2006 in Manisa. People, who were chosen by random sampling, were given questionnaires, and the study was completed by conducting the following statistical procedures: Chi-square, arithmetic mean study, percentages and confidence intervals. The results of this study revealed that the demographic elements and socio-cultural structure of Manisa people, play an important role in shaping their level of interest in sports. However, when we make a general overview of the results, it is observed that the opinion of the people for sports activities is positive. In this respect, the people of the region have important expectations both from the local and central administrations to promote and spread the mass sports and increase the number of sports facilities for the benefit of the people.
Keywords: Beden Eğitimi ve Spor; Spor